A new species of Nyctibatrachus Boulenger (Amphibia: Anura: Nyctibatrachidae) from the Eravikulam National Park, Kerala, India - Radhakrishnan, C.; Dinesh, K. P.; Ravichandran, M. S. (Zootaxa, 2007)
A new species of Indian nyctibatrachid frog, Nyctibatrachus sholai (Amphibia: Anura), is described based on a series of 6 specimens from the Eravikulam National Park, southern Western Ghats of the State Kerala, India. The new species is compared with all known congeners. It is diagnosed by the following combination of characters: skin with glandular corrugations with metallic green coloration; head wider than long; snout not projecting beyond mouth; irregular longitudinal corrugations on the dorsum and extending up to the dorsal surface of arms and thighs; faint supratympanic fold; a fold from posterior corner of eye to angle of jaw clearly defined; tympanum partially visible; webbing on toes ¼ th , except that on 3 rd toe reaching penultimate subarticular tubercle; tips of digits and toes flattened to form minute disks with dorsal longitudinal grooves; femoral gland present. The largest specimen in the type series has a snout-vent length of 22.1 mm. A key to the species of Nyctibatrachus is provided.